A Multiplex Asymmetric Reverse Transcription-PCR Assay Combined With an Electrochemical DNA Sensor for Simultaneously Detecting and Subtyping Influenza A Viruses - Xu, Lili; Jiang, Xiwen; Zhu, Yun; Duan, Yali; Huang, Taosheng; Huang, Zhiwen; Liu, Chunyan; Xu, Baoping; Xie, Zhengde (Frontiers in Microbiology, 2018)
The reliable and rapid detection of viral pathogens that cause respiratory infections provide physicians several advantages in treating patients and managing outbreaks. The Luminex respiratory virus panel (RVP) assay has been shown to be comparable to or superior to culture/direct fluorescent-antibody assays (DFAs) and nucleic acid tests that are used to diagnose respiratory viral infections. We developed a multiplex asymmetric reverse transcription (RT)-PCR assay that can simultaneously differentiate all influenza A virus epidemic subtypes. The amplified products were hybridized with an electrochemical DNA sensor, and the results were automatically acquired. The limits of detection (LoDs) of both the Luminex RVP assay and the multiplex RT-PCR-electrochemical DNA sensor were 101 TCID50 for H1N1 virus and 102 TCID50 for H3N2 virus. The specificity assessment of the multiplex RT-PCR-electrochemical DNA sensor showed no cross-reactivity among different influenza A subtypes or with other non-influenza respiratory viruses. In total, 3098 respiratory tract specimens collected from paediatric patients diagnosed with pneumonia were tested. More than half (43, 53.75%) of the specimens positive for influenza A viruses could not be further subtyped using the Luminex RVP assay. Among the remaining 15 specimens that were not subtyped, not degraded, and in sufficient amounts for the multiplex RT-PCR-electrochemical DNA sensor test, all (100%) were H3N2 positive. Therefore, the sensitivity of the Luminex RVP assay for influenza A virus was 46.25%, whereas the sensitivity of the multiplex RT-PCR-electrochemical DNA sensor for the clinical H1N1 and H3N2 specimens was 100%. The sensitivities of the multiplex RT-PCR-electrochemical DNA sensor for the avian H5N1, H5N6, H9N2, and H10N8 viruses were 100%, whereas that for H7N9 virus was 85.19%. We conclude that the multiplex RT-PCR-electrochemical DNA sensor is a reliable method for the rapid and accurate detection of highly variable influenza A viruses in respiratory infections with greater detection sensitivity than that of the Luminex xTAG assay. The high mutation rate of influenza A viruses, particularly H3N2 during the 2014 to 2016 epidemic seasons, has a strong impact on diagnosis. A study involving more positive specimens from all influenza A virus epidemic subtypes is required to fully assess the performance of the assay.